Global Morphology Distortion of the 2021 October 9 Coronal Mass Ejection from an Ellipsoid to a Concave Shape - Liping Yang; Chuanpeng Hou; Xueshang Feng; Jiansen He; Ming Xiong; Man Zhang; Yufen Zhou; Fang Shen; Xinhua Zhao; Huichao Li; Yi Yang; Xiaojing Liu (The Astrophysical Journal, 2023)
This paper presents a study of a 2021 October 9 coronal mass ejection (CME) with multipoint imaging and in situ observations. We also simulate this CME from the Sun to Earth with a passive tracer to tag the CME’s motion. The coronagraphic images show that the CME is observed as a full halo by SOHO and as a partial halo by STEREO-A. The heliospheric images reveal that the propagation speed of the CME approaches about 1° hr ^−1 , suggesting a slow CME. With simulated results matching these observation results, the simulation discloses that as the CME ejects from the Sun out to interplanetary space, its global morphology is distorted from an ellipsoid to a concave shape owing to interactions with the bimodal solar wind. The cross section of the CME’s flux rope structure transforms from a circular shape into a flat one. As a result of the deflection, the propagation direction of the CME is far away from the Sun–Earth line. This means that the CME flank (or the ICME leg) likely arrives at both Solar Orbiter and the L1 point. From the CME’s eruption to 1 au, its volume and mass increase by about two orders and one order of magnitude, respectively. Its kinetic energy is about 100 times larger than its magnetic energy at 1 au. These results have important implications for our understanding of CMEs’ morphology, as well as their space weather impacts.